KONTRIBUSI SUPERVISI PENDIDIKAN ISLAM TERHADAP PENINGKATAN KUALITAS PENDIDIKAN MULTIKULTURAL DI SEKOLAH ISLAM - M. Ali Yusron; Mujamil Qomar; Akhyak Akhyak (Universitas Islam Negeri (UIN) Sumatera Utara, 2024)
This study aims to explore the contribution of Islamic educational supervision in improving the quality of multicultural education in Islamic schools. The background of this study is based on the importance of multicultural education in the context of pluralistic Indonesian society, as well as the need to make educational supervision a means of teacher development in creating inclusive and tolerant learning. Islamic schools have a responsibility to instill Islamic values that are in line with the principles of diversity and social justice. Therefore, Islamic educational supervision needs to be directed to support the strengthening of multicultural values in educational practices. This research method uses a qualitative approach with literature review techniques. Data were obtained through analysis of scientific literature in the form of journals, books, and academic documents that are relevant to the theme of Islamic educational supervision and multicultural education. The analysis was carried out descriptively with the steps of identification, classification, synthesis, and interpretation of findings from various sources. The results of the study indicate that Islamic educational supervision contributes to five main aspects: improving teacher competence in a multicultural perspective, integrating Islamic values with the principle of inclusivity, establishing a tolerant school climate, transforming school culture, and developing leadership based on Islamic values. The conclusion of this study confirms that supervision of Islamic education carried out effectively and contextually can be a strategic instrument in supporting the realization of quality multicultural education in Islamic schools.